Thermographic and anthropometric assessment of electrical stimulation on localized body fat - Graciele Guimarães Pitelli Aroca; Larissa Granato Viana; Rafaela Ferreira de Araújo Costa; Dalilia Schmildt; Ligia de Sousa
Abstract Introduction: Adiposity is defined as the accumulation of energy reserves within the adipose tissue at specific body sites. Low-frequency electrical stimulation elicits lipolysis. When applied by insertion of needles into the dermis-hypodermis junction, it leads to a modification of the interstitial space, favoring metabolic changes and lipolysis. Objective: To investigate the effects of electrical stimulation on body fat localized to the abdomen and flanks. Methods: Randomized, controlled clinical trial consisted of two groups of women with body fat localized to the abdomen and flanks. The intervention group (IG) was made up of 9 women (± 24,77 years) who received ten sessions of electrical stimulation, whereas the control group (CG) was made up of 7 women (± 21,8 years) who did not receive electrical stimulation. Perimetric, adipometric and thermographic data were collected before and after the intervention. Data were analyzed using the Shapiro-Wilk test, t test, one-way ANOVA. The significance level was set at p < 0,05. Results: There were statistically significant differences between the intervention and control groups in the assessment immediately following intervention (IG: 33.08 ± 1.00; CG: 30.83 ± 1.5; p = 0.002), 15 minutes following intervention (IG: 33.05 ± 0.48; CG: 30.40± 1.24; p < 0.0001) and at the endpoint (IG: 32.22 ± 14.20; CG: 30.53 ± 1.34; p=0.005) for the thermographic data. For the anthropometric variables, there were no statistically significant differences before and after treatment. Conclusion: Electrical stimulation evokes a significant increase in the temperature of the subcutaneous tissue.